Analisis potensi interaksi antar obat pada resep polifarmasi di apotek kota Bandung - Aulia, Nazela Constantia Hilyatul; Subarnas, Anas (Journal of Pharmaceutical and Sciences, 2024)
Problems that can occur in drug prescribing patterns are Drug Related Problems (DRP), which can affect the patient's clinical condition. One type of DRP that often occurs is drug interactions. Drug interactions cause changes in the effect of a drug due to the presence of other drugs taken simultaneously, which will cause a decrease in the therapeutic effect of the drug and increase toxicity in the body. Therefore, drug interactions were identified from general practitioner prescriptions at one of the Bandung City pharmacies. General practitioner prescription data was taken from July-September 2023 at the pharmacy in Bandung City, namely 202 prescriptions, and categorized based on their severity using the website drug, com. The results of this identification showed that 32 prescriptions had interactions between drugs with different levels of severity, showing that 2 prescriptions (6%) had drug interactions of different types. In the majority, 24 prescriptions (75%) had moderate drug-type interactions, and 6 recipes (19%) had minor.